The inhibition effect of water on the purification of natural gas with nanoporous graphene membranes - Nieszporek, Krzysztof; Pańczyk, Tomasz; Nieszporek, Jolanta (Beilstein Journal of Nanotechnology, 2018)
Molecular dynamics simulations are used to investigate the inhibiting effect of water on the natural gas separation with nanoporous graphene. The membrane separation process involves CH4 + N2 mixtures with and without the addition of water. The results show that water is able to form hydrogen bonds with nitrogen atoms located in a nanopore rim. This effect causes a decrease of separation selectivity as well as a reduction of gas permeation. In the extreme case, when the nanopore rim contains only nitrogen atoms, water agglomerates at the center of the nanopore and effectively closes down the permeation path. The conclusions are confirmed by the analysis of stability and kinetics of hydrogen bonds.
Keywords: graphene membrane; hydrogen bonds; molecular dynamics; separation